2019
DOI: 10.1016/j.pld.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating germinability of eight desert halophytes under long-term seed storage: Implications for conservation

Abstract: Ex situ conservation in seed banks is a potential complementary conservation strategy for native plant species. It is well established that ex situ seed banking of native wild plants prolongs seed viability and thereby preserves genetic and species diversity for future use. We evaluated ex situ storage potential of eight halophytic species from deserts in the United Arab Emirates (UAE) by studying seed germination. Specifically, we examined the germinability of freshly collected seeds and seeds stored for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…There are many Halophytes in desert area. The results showed that the germination patterns of halophytes are different; generally, most halophytes maintain seed vigor under long-term storage, thus increasing the possibility of successful seed recovery [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many Halophytes in desert area. The results showed that the germination patterns of halophytes are different; generally, most halophytes maintain seed vigor under long-term storage, thus increasing the possibility of successful seed recovery [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…This response to light seems to be phylogenetically fixed within the genus Ferocactus , but also within the tribe Cacteae, where more genera have the same response to light, such as species of Echinocactus and Mammillaria (see Rojas‐Aréchiga et al, 2013). Although light sensitivity of seeds can change through time (Gairola et al, 2019), making seeds able to germinate under different light conditions at different times, we demonstrated that the photoblastic response of F. peninsulae did not change with storage time. The requirement for light remained through time, which is a seed trait that makes seeds prone to remain in the soil seed bank.…”
Section: Discussionmentioning
confidence: 47%
“…Some aspects of seed biology, such as germination requirements, dormancy mechanisms, and longevity, are essential to plant population management and conservation programs (Gairola et al, 2019). Knowledge on seed dormancy is important to understand plant dynamics in their habitat as well as for propagation studies, conservation programs, and rehabilitation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptations exhibited by S. vermiculata resulted in its wide spatial distribution in arid environments (Guma et al 2010, Boulos 1991, and its presence in variable habitats (African Plant Database, 2019). S. vermiculata produces small seeds and have limited dispersal due to the lack of dispersal structures (Gairola et al 2019), unlike other members of the family Chenopodiaceae possessing winged accrescent sepals inyact to the seeds, enhancing wind dispersal (Zhu et al 2003). This limited dispersal of S. vermiculata describes the threshold when adaptation fail (Polechova and Barton, 2015 Al-Tohamy, R., Ali, S.S., Saad-Allah, K., Fareed, M., Ali, A., El-Badry, A., El-Zawawy, N.A., Wu, J., Sun, J., Mao, G. and Rupani, P.F.…”
Section: Discussionmentioning
confidence: 99%